Distributions of Globotriaosylceramide Isoforms, and Globotriaosylsphingosine and Its Analogues in an α-Galactosidase A Knockout Mouse, a Model of Fabry Disease. - Hideaki Sueoka; Mikio Aoki; Takahiro Tsukimura; Tadayasu Togawa; Hitoshi Sakuraba (PLoS ONE)
Fabry disease is caused by deficient activity of α-galactosidase A (GLA) and characterized by systemic accumulation of glycosphingolipids, substrates of the enzyme. To gain insight into the pathogenesis of Fabry disease based on accumulated substrates, we examined the tissue and plasma distributions of globotriaosylceramide (Gb3) isoforms, and globotriaosylsphingosine (lyso-Gb3) and its analogues in a GLA knockout mouse, a model of Fabry disease, by means of liquid chromatography-mass spectrometry and nano-liquid chromatography-tandem mass spectrometry, respectively. The results revealed that the contents of these substrates in the liver, kidneys, heart, and plasma of GLA knockout mice were apparently higher than in those of wild-type ones, and organ specificity in the accumulation of Gb3 isoforms was found. Especially in the kidneys, accumulation of a large amount of Gb3 isoforms including hydroxylated residues was found. In the GLA knockout mice, the proportion of hydrophobic Gb3 isoforms was apparently higher than that in the wild-type mice. On the other hand, hydrophilic residues were abundant in plasma. Unlike that of Gb3, the concentration of lyso-Gb3 was high in the liver, and the lyso-Gb3/Gb3 ratio in plasma was significantly higher than those in the organs. The concentration of lyso-Gb3 was apparently higher than those of its analogues in the organs and plasma from both the GLA knockout and wild-type mice. This information will be useful for elucidating the basis of Fabry disease.